Kölner Herbstsalon 1982. (Köln : Josef-Haubrich-Kunsthalle, 1982)
Beck, Klaus ; Büttner, Werner ; Hitzler, Franz ; Kiecol, Hubert ; Lüpertz, Markus ; MÜnch, Horst ; Oehlen, Markus ; Runge, Stephan ; Schulze, Andreas
Kölner Herbstsalon 1982, Josef-Haubrich-Kunsthalle, Köln, 12. - 29. August 1982
boek